Estado secular : pluralidad e identidad común (2017)
This text has four sections. The first section expose Charles Taylor's conception of the secular state. Additionally, it brings some concepts from Taylor's philosophy of language, which allows to understand how an individual point of view and the public space are configured. The second section presents Talal Asad's critic of the secular state. This critic can elucidate some problematic assumptions that emerge from accepting a liberal comprehension of the state. The third section tries to provide some considerations from Taylor's posture that may answer Asad's critic; however, recognizing the tensions and limitations that remain present between these perspectives. The last section offers an interpretation of Taylor's philosophy of language and his conception of the secular state, in order to expose how it is possible to reconfigure our identity as individuals and as a society.